Efeito de fitorreguladores e de substratos na propagação vegetativa de camu-camu, por meio de estacas - Silva, Francisco Wolney Costa da (2009)
Camu-camu (Myrciaria dubia) is an Amazonia species whose fruits present a high those of acid ascorbic, between 1380 and 6112 mg.100g-1 of dry pulp of the fruit, characteristic that awakes interest in the food industry. To be cultivated, we have therefore, the answers to the use of indole butyric acid (IBA), naphthalene acetic acid (NAA) and indole acetic acid (IAA) in the concentration of 0, 1000 mg.L-1, 2000 mg.L- 1, 3000 mg.L-1 , 4000 mg.L-1 and 5000 mg.L-1 applied for fast immersion as well as the use of vermiculite, sand, carbonized rice rind and plantmax® used in the simple form or as a compound on the roots of the camu-camu, was studied in experiments in Boa Vista RR. Semi-hardwood cuttings were used take from branches of the plants, collected on the edge of the Cauamé river. The cutting or of standard size of 20cm in length and 0,8cm in diameter, leaving a pair of leaves at. The factorial design was of 3x5, consisted of growth regulators IBA, NAA and IAA with five concentrations levels, four replicators and 12 cuttings per plot. For flu second experiment, the treatments were made by ten substrates, using the simple or combined form. The constant practice of plant growth regulators promoted the increase in the number of rooted cuttings. However no significant effect of the use of the different concentrations of fitoregulators IBA and IAA, was not observed. The highest percentage of rooting was obtained with the concentration of 3000 mg.L-1 of NAA (12%). The utilization of sand combined with rice husk or with vermiculite yielded the highest number of rooted cuttings (16%). The vermiculite substract, utilized in the simple or combined form, resulted in even a smaller percentage of rooting.